The differential role of HTRA1 in HPV-positive and HPV-negative cervical cell line proliferation - Stuqui, Bruna [UNESP] (2016)
Background: High-risk human papillomaviruses (HPVs) are strongly associated with the development of some malignancies. The E6 and E7 viral oncoproteins are the primary proteins responsible for cell homeostasis alteration and immortalization. Furthermore, the E6 protein from high-risk HPVs can interact with the PDZ (PSD-90/Dlg/ZO-1) domains of cellular proteins, triggering cell transformation. One protein that is associated with pathological conditions and has a PDZ domain is the protease HTRA1 (high temperature requirement 1). This protein is poorly expressed in some cancers, suggesting a tumor suppressor role. The aim of this study was to evaluate the effect of HTRA1 overexpression in HPV16-positive (CasKi) and HPV-negative (C33) cervical cell lines. Methods: The cells were transfected with a vector containing the HTRA1 ORF or an empty vector. HTRA1 overexpression was confirmed by qRT-PCR. The cells were subjected to cell proliferation, colony formation, apoptosis and cell cycle assays. Results: C33 cells expressing HTRA1 grew significantly fewer colonies and showed less proliferation than cells without HTRA1 expression. In contrast, in the CasKi cells overexpressing HTRA1, there was an increase in the cell growth rate and in the colonies density compared to cells expressing low levels of HTRA1. An apoptosis assay showed that HTRA1 does not interfere with the apoptosis rate in these cells. A cell cycle immunofluorescence assay revealed more CasKi cells overexpressing HTRA1 in the S phase and more C33 HTRA1-transfected cells in the G0/G1 phase, suggesting that HTRA1 plays different roles in the cell cycle progression of these cells. Conclusions: HTRA1 overexpression prevents cell proliferation in the HPV-negative cell line and increases cell proliferation in the HPV-positive cell line. Although the E6/HTRA1 interaction has already been described in the literature, more studies are required to confirm whether the present functional findings are a result of this interaction.